EFEKTIVITAS DEEP LEARNING BERBANTU MEDIA FRACTION BOARD TERHADAP HASIL BELAJAR PECAHAN SISWA KELAS IV SDN KATELAN 1 - Zaitun, Alinda; Sari, Elok Fariha (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This study aims to determine (1) the mastery of student learning outcomes using Deep Learning assisted by the Fraction Board, (2) the differences in student learning outcomes between Deep Learning assisted by the Fraction Board and conventional learning, and (3) the effectiveness of Deep Learning assisted by the Fraction Board on student learning outcomes. This study is a quantitative study using a quasi-experimental design, specifically a nonequivalent control group design. The research sample consisted of two classes selected using purposive sampling. The instrument used was a test, and the data obtained were analyzed using prerequisite tests, namely normality and homogeneity tests. The results of the prerequisite tests indicated that the sample was normally distributed and homogeneous. Data analysis utilized descriptive statistics, the one-sample t-test, the independent samples t-test, and the N-Gain test. The results of the study showed a significant difference between the two classes with a Sig. value of 0.001 < 0.05. The average N-Gain score of the experimental class was 58.3%, which falls into the fairly effective category. Meanwhile, the control class only reached 38.3%, which falls into the ineffective category. This study shows that Deep Learning assisted by the Fraction Board medium has been proven to improve student learning outcomes.